Efficient Implementation of Automaton Functors for the Verification of Graph Transformation Systems - Blume, Christoph (Electronic Communications of the EASST, 2011)
In this paper we show new applications for recognizable graph languages to invariant checking. Furthermore we present details about techniques we used for an implementation of a tool suite for (finite) automaton functors which generalize finite automata to the setting of recognizable (graph) languages. In order to develop an efficient implementation we take advantage of Binary Decision Diagrams (BDDs).